2015
DOI: 10.1111/ajd.12190
|View full text |Cite
|
Sign up to set email alerts
|

Does ear keloid formation depend on the type of earrings or piercing jewellery?

Abstract: The ear is one of the most common sites of keloid formation, usually associated with the wearing of earrings. However, although this is a small perforating lesion that is equal on both sides, keloids are bigger and more prevalent on the posterior surface. In this study, 141 keloids were evaluated, most of which were located on the posterior surface of the earlobe and caused by the piercing of the ear. Most of the earrings and piercing jewellery used had metallic backs. The more frequent occurrence of earlobe k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
0
5
0
1
Order By: Relevance
“…Piercing jewelry material, earring backs, the type of piercing procedure, and complications related to piercing at the time of the procedure may contribute to keloid formation. 2 None of our patients had a complication related to piercing at the time of the procedure. In our cases, keloid formation was more likely to be associated with a cartilage injury.…”
mentioning
confidence: 68%
“…Piercing jewelry material, earring backs, the type of piercing procedure, and complications related to piercing at the time of the procedure may contribute to keloid formation. 2 None of our patients had a complication related to piercing at the time of the procedure. In our cases, keloid formation was more likely to be associated with a cartilage injury.…”
mentioning
confidence: 68%
“…7 Another study of 141 ear keloids found a possible correlation between ear keloids and metallic backs of earrings, which leads to a local neurogenic inflammation further leading to more frequency of keloids over posterior surface of the ear lobule. 8…”
Section: Discussionmentioning
confidence: 99%
“…Keloid formation after earring placement may be predisposed by extrinsic trauma to the region, allergies to earring materials, infection due to non-sterile piercing conditions or otherwise, mechanical force from contact with a pillow during sleep, and the weight of the earring. [2][3][4][5] It is unclear of the predisposing history in this patient's case of keloid scarring; however, poor healthcare-literacy as evidenced by attempted self-amputation of the scar likely contributed to the extent of keloid formation and necrosis seen. Additionally, incarcerated and formerly incarcerated populations may present at later disease stages and often have lower levels of health literacy than the free world population.…”
Section: Images In…mentioning
confidence: 94%